A new qualitative RT-PCR assay detecting SARS-CoV-2 - Marco Favaro; Walter Mattina; Enrico Salvatore Pistoia; Roberta Gaziano; Paolo Di Francesco; Simon Middleton; Silvia D’Angelo; Tullio Altarozzi; Carla Fontana (Scientific Reports, 2021)
Abstract The world is facing an exceptional pandemic caused by SARS-CoV-2. To allow the diagnosis of COVID-19 infections, several assays based on the real-time PCR technique have been proposed. The requests for diagnosis are such that it was immediately clear that the choice of the most suitable method for each microbiology laboratory had to be based, on the one hand, on the availability of materials, and on the other hand, on the personnel and training priorities for this activity. Unfortunately, due to high demand, the shortage of commercial diagnostic kits has also become a major problem. To overcome these critical issues, we have developed a new qualitative RT-PCR probe. Our system detects three genes—RNA-dependent RNA polymerase (RdRp), envelope (E) and nucleocapsid (N)—and uses the β-actin gene as an endogenous internal control. The results from our assay are in complete agreement with the results obtained using a commercially available kit, except for two samples that did not pass the endogenous internal control. The coincidence rate was 0.96. The LoD of our assay was 140 cp/reaction for N and 14 cp/reaction for RdRp and E. Our kit was designed to be open, either for the nucleic acid extraction step or for the RT-PCR assay, and to be carried out on several instruments. Therefore, it is free from the industrial production logics of closed systems, and conversely, it is hypothetically available for distribution in large quantities to any microbiological laboratory. The kit is currently distributed worldwide (called MOLgen-COVID-19; Adaltis). A new version of the kit for detecting the S gene is also available.